PROBLEM OF ECOLOGICAL HAZARD REDUCTION - Mariana A. Basilaia (Advanced Engineering Research)
The actual problems of ecological hazard, ways of ecological hazard reduction, and harmonious interaction of society and nature in the "man-nature" system are  considered.